Integrity of Financial Statements: Does Ownership Structure Matter? (Empirical Study of LQ45 Index Companies Listed on the Indonesia Stock Exchange Consecutive Years 2019-2023) - Muhammad Munandar; Setianingtyas Honggowati (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
This study aims to examine the connection between ownership structure and financial statement integrity using proxies institutional, foreign, and family ownership and control variables such as profitability, size, and leverage. This study used a quantitative descriptive method. The LQ-45 indexed companies that were listed on the IDX between 2019 and 2023 make the study's population. According to the study's findings, family and institutional ownership have an impact on financial statements' integrity, which could increase their credibility. On the other hand, foreign ownership has no effect on the integrity of financial statements. The agency theory, which highlights the need of efficient oversight and management of business operations to guarantee the integrity of financial statements, is supported by these results. Additionally, it motivates capital market supervisory bodies or regulators to take into account measures that promote accountability and openness in financial reporting.